Subsurface Water Retention Technology (SWRT) for Water Saving and Growing Tomato in Iraqi Sandy Soils - Aoda, Mahdi Ibrahim; Ati, Alaa Salih; AL-Rawi, Shatha Salim; Smucker, Alvin J. M. (Sulaimani Journal for Pure and Applied Sciences, 2018)
A study was carried out to assess the impact of using SWRT on irrigation water use efficiency IWUE and yields of tomato crop. Experiments were performed by planting tomato in greenhouses during the spring season of 2014 at two locations in Iraq. One location was at north of Baghdad (latitude 33ᵒ 38' 58.44" north and longitude 44ᵒ 24' 17.74"east) at Jaded at Al-Shat, Diyala Province. The other location was at Najaf Province (latitude 32ᵒ 07' 37.80" north and longitude 44ᵒ 19' 44.74" east). Soils of the both locations are classified as sandy loam in texture. Four treatments (SWRT, organic matter, tillage and no–tillage farming) were used to represent different tillage practices in studied locations. The experimental design was randomized complete blocked design RCBD with four replications. Irrigation scheduling was performed according to soil moisture content as 50-55% of available water was depleted then irrigation water was added from subsurface drip system to bring soil moisture content back to field capacity. Soil sensors 5TE and GS3 from the Decagon Devices, USA were used to measure volumetric water content hourly. Water balance equation was used to determine the actual water consumption during each stage of plant growth for the whole season. The results showed that the amount of irrigation water and plant yield varied with treatment. Average tomato yield per plant were 3.53, 3.28, 3.26 and 3.06 kg for Diyala location and 3.03, 2.49, 2.37 and 2.05 kg for Najaf location for treatments SWRT, organic matter, no–tillage and tillage treatments, respectively. Depths of irrigation water for season were 307, 486, 502 and 502 mm for Diyala location and 259, 433, 449 and 449 mm for Najaf location for treatments SWRT, organic matter, no – tillage and tillage treatments, respectively. Values of IWUE for tomato at Diyala location were 7.54, 4.54, 4.36 and 4.09 kg m-3 for SWRT, organic matter, tillage and no – tillage treatments, respectively. This shows that SWRT is higher in IWUE by 70, 89 and 77% than organic matter, tillage and no – tillage treatments, respectively. Similar trend of IWUE values for tomato in Najaf was obtained which were 7.78, 3.72, 3.55 and 3.07 kg m-3 for SWRT, organic matter, tillage and no–tillage treatments, respectively, as an increase of SWRT by 112, 156 and 122% over organic matter, tillage and no – tillage treatments, respectively.
Keywords: Subsurface water retention technology Tomato Iraqi sandy soils